Findings From the Analysis of the American College of Nurse‐Midwives' Membership Surveys: 2009 to 2011. (23rd July 2013) - Schuiling, Kerri D.; Sipe, Theresa A.; Fullerton, Judith
<x xml:space="preserve">Abstract</x> Introduction The American College of Nurse‐Midwives (ACNM) Core Data Survey is an annual membership survey that collects demographic and selected workforce data about certified nurse‐midwives (CNMs), certified midwives (CMs), and students enrolled in midwifery education programs accredited by the Accreditation Commission for Midwifery Education. These data are aggregated and published every 3 years. This article presents findings from the analysis of membership data for the years 2009 to 2011. Methods An online survey is sent annually to all ACNM members who provide ACNM with an e‐mail address. The survey instrument for 2009 to 2011 focused on 5 categories: demographics, certification, education, employment, and licensure except for 2011, in which licensure data were collected separately. Results ACNM members responding to the surveys during 2009, 2010, and 2011 continued to remain predominantly white and female. The average age of CNMs/CMs in 2011 was 51.2 years. The majority had a master's degree as their highest degree, and 9.3% had a doctoral degree. Approximately two‐thirds of respondents in each of the 3 survey years identified attendance at births as one of their primary responsibilities. Discussion Very little change in diversity was observed over the 3 survey years. The number of CNMs earning the doctor of nursing practice degree is increasing, whereas other doctoral degree categories remain stable. The majority of CNMs/CMs continue to identify a broad domain of clinical midwifery practice as their primary responsibility in their employment. The majority of respondents attend births, but the proportion has been decreasing slightly over time. Salaries for midwives continue to rise, but the reasons for this are unclear.